Interaction between Paracoccidioides brasiliensis conidia and the coagulation system : involvement of fibrinogen (2013)
ABSTRACT: The infectious process starts with an initial contact between pathogen and host. We have previously demonstrated that Paracoccidioides brasiliensis conidia interact with plasma proteins including fibrinogen, which is considered the major component of the coagulation system. In this study, we evaluated the in vitro capacity of P. brasiliensis conidia to aggregate with plasma proteins and compounds involved in the coagulation system. We assessed the aggregation of P. brasiliensis conidia after incubation with human serum or plasma in the presence or absence of anticoagulants, extracellular matrix (ECM) proteins, metabolic and protein inhibitors, monosaccharides and other compounds. Additionally, prothrombin and partial thromboplastin times were determined after the interaction of P. brasiliensis conidia with human plasma. ECM proteins, monosaccharides and human plasma significantly induced P. brasiliensis conidial aggregation; however, anticoagulants and metabolic and protein inhibitors diminished the aggregation process. The extrinsic coagulation pathway was not affected by the interaction between P. brasiliensis conidia and plasma proteins, while the intrinsic pathway was markedly altered. These results indicate that P. brasiliensis conidia interact with proteins involved in the coagulation system. This interaction may play an important role in the initial inflammatory response, as well as fungal disease progression caused by P. brasiliensis dissemination.